(untitled) (Kerala Journal of Psychiatry, 2021)
Background: Neurocognitive studies during the euthymic phase of bipolar disorder have shown persistent cognitive deficits in 32% of patients. There is limited evidence in the Indian literature regarding this area. Neurocognitive impairment can significantly affect the overall functional recovery of these individuals. Understanding potential factors contributing to neurocognitive impairment in bipolar disorder is essential to develop prevention strategies and effective treatments. Methods: A total of 50 patients with bipolar disorder currently in euthymic phase for the last three months with a minimum duration of illness of two years and current Young Mania Rating Scale<11 and Hamilton Depression Rating Scale <8 currently on medications were administered various cognitive tests namely digit span test forward and backward, digit symbol substitution test and Trail making test A and B. The study was completed within a period of 6 months after getting approval from the institutional ethics committee. Results: Patients with bipolar disorder, in remission, have cognitive impairment in attention, memory and executive functioning. More than 50% of the patients could perform digit span test forward more than five digits, and in the case of the digit span test backwards, more than 50% of patients could perform only less than or equal to three digits. In the Trail Making tests A and B, 66% of the patients could perform within </=78seconds, and 62% could perform within </=273 seconds, respectively. Only 4% of the patients could complete 49 squares in the Digit symbol substitution test. Conclusion: Findings of the current study shows evidence of cognitive impairment in euthymic bipolar patients.